Analysis of Human, Environmental, and Vehicle Factors Affecting Traffic Accident Severity in Jurisdiction of Metro Jaya Police - Aditya Veda (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
The jurisdiction of the Jakarta Metropolitan Police (Polda Metro Jaya) is one of the areas experiencing traffic accident problems. Traffic accidents in the Jakarta Metropolitan Police jurisdiction can involve two-wheeled vehicles, four-wheeled vehicles, trucks, and even pedestrians. Accidents can be assessed based on the severity of the accident, usually classified as mild, moderate, and severe. Accident severity in this study focuses on human, environmental, and vehicle factors. This study aims to determine the most important sub-factors that increase the severity of traffic accidents in the Jakarta Metropolitan Police jurisdiction. The theories used in this study are transportation theory and human error theory. This study uses accident data in the form of the Integrated Road Safety Management System (IRSMS) from the Police, which is tested using Structural Equation Modeling (SEM), and validated using questionnaire data collected through a Google Form survey analyzed using partial least squares (PLS). The results of the IRSMS data analysis indicate that attention and drowsiness are strong predictors of increased severity. The results of the survey analysis indicate that drowsiness and vehicle age are significant predictors of severity. The validation results of the Integrated Road Safety Management System (IRSMS) data analysis and questionnaire provide a comprehensive picture of the complexity of the causes of the severity of accidents that can be experienced.